Experimental and computational investigations on the high binding-selectivity of pyrimidine derivatives by a pillar[5]arene. Issue 12 (2nd December 2018) - Zhang, Qian; Li, Ke-Qing; Yang, Jun-Hui; Qu, Gui-Rong; Ma, Na-Na; Guo, Hai-Ming
ABSTRACT: The binding selectivity of an adenine-monofunctionalized pillar[5]arene (H ) with a series of pyrimidine derivatives were investigated through 1 H NMR experiments and density functional theory (DFT) study. High binding-selectivity was demonstrated. Typically, H displayed very strong binding strength with 6-(2, 4-dioxo-3, 4-dihydropyrimidin-1 (2 H )-yl)hexanenitrile (G1 ) [ Ka >10 5  M −1 ], up to about 3000-fold as compared with 1-hexylpyrimidine-2, 4(1 H, 3 H )-dione (G5 ) [ Ka  = 31 M −1 ]. The strong binding ability ofH withG1 was due to the cooperative multiple hydrogen bond, dipole-dipole, C-H···π and π···π interactions. The high binding-selectivity was also verified by calculation results. The calculated interaction energy ( ΔE i ) ofG1 ⊂H was −12.92 Kcal·mol −1 while that ofG5 ⊂H was −2.85 Kcal·mol −1 . Graphical Abstract: